Decree of the president of the Arab Republic of Egypt No. 337 of the year 1997 Concerning the Approval of the Agreement To Facilitate and Develop Trade Among Arab States Signed in Tunisia On 27/2/1981 and its Executive program which was Adopted by the Arab League Economic and social Council om its 58th Round by Resolution No. 1317 Dated 19/2/1997 - Egypt (2025)
Decree of the President of the Arab Republic of Egypt No. 337 of the Year 1997 concerning the approval of the agreement to facilitate and develop trade among states signed in Tunisia on 27/2/1981, and its executive program which was adopted by the Arab league economic and social council on its 58th round by resolution no. 1317 dated 19/2/1997 – Reservation of the Arab Republic of Egypt on the provision of article 20 of the agreement to facilitate and develop trade among the Arab states – قرار رئيس جمهورية مصر العربية رقم 337 لسنة 1997 بشأن الموافقة على اتفاقية تيسير وتنمية التبادل التجارى بين الدول العربية الموقعة فى تونس 27/2/1981 وبرنامجها التنفيذى الذى أقره المجلس الاقتصادى والاجتماعى فى دورته الثامنة والخمسين بموجب قراره رقم 1317 بتاريخ 19/2/1997